Erratum - Castillo-Urquiagal, Walter (2024)
In the article “Placental insufficiency in term and post-term pregnancy with normal fetal growth and adverse outcome” in the Peruvian Journal of Maternal Perinatal Research 2017 6 (2): 31-36.